Reporting quality of polycystic ovary syndrome practice guidelines based on the RIGHT checklist. Issue 42 (16th October 2020) - Li, Hongzhu; Zhang, Yu; Lu, Liming; Yi, Wei
Abstract: Background: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder involving hyperandrogenism, menstrual disorder, metabolic problems, infertility, obesity, and acne. The main aim of this study was to assess the reporting quality of clinical practice guidelines (CPGs) in the field of PCOS to provide a reporting specification for this study. Methods: We evaluated the reporting quality of clinical guidelines of PCOS using the Reporting Items for Practice Guidelines in HealThcare (RIGHT) checklist. Nine databases and 3 medical associations were searched. These included Medline, Embase, PubMed, National Institute for Health and Care Excellence (NICE), Guidelines International Network (GIN), National Guideline Clearinghouse (NGC), China National Knowledge Infrastructure, Wanfang and Chinese Science, and Technology Journal Database (VIP). Three medical associations included the European Society of Human Reproduction and Embryology, the American Society for Reproductive Medicine and the Agency for Healthcare Research and Quality. Two independent authors assessed the reporting quality of PCOS CPGs by the RIGHT checklist, and Spearman's correlation was used to assess inter-rater reliability. Results: Twelve PCOS CPGs were included. On average, 20.0 (57.1%) of the 35 items in the RIGHT checklist were reported. All items were fully reported by one of these CPGs. The number of reported items ranged from 10 (28.6%) to 35 (100%). Overall, 16.7%, 66.7%, and 16.7% of included guidelines were of high, medium, and low quality, respectively. The reporting proportions of the 7 domains (i.e., Basic information, Background, Evidence, Recommendations, Reviewand quality assurance, Funding and declaration and management of interests, and Other information) in the RIGHT checklist were 62.0%, 69.1%, 53.3%, 60.7%, 33.3%, 31.2%, and 69.4%, respectively. Conclusions: The evaluation of these CPGs by the RIGHT checklist revealed that the reporting quality varied among guidelines. Low quality items were the processes of evidence decision and the declaration of funding in most included CPGs. Guideline developers should pay more attention to these items to disseminate and implement better guidelines in near future. Trial registration number: registration at PROSPERO CRD42020163435